Advances in molecular characterization of myeloid proliferations associated with Down syndrome - Li, Jixia; Kalev-Zylinska, Maggie L. (Frontiers in Genetics, 2022)
Myeloid leukemia associated with Down syndrome (ML-DS) has a unique molecular landscape that differs from other subtypes of acute myeloid leukemia. This malignant disease is frequently preceded by a myeloproliferative neoplastic condition called transient abnormal myelopoiesis (TAM) that disrupts megakaryocytic differentiation. Over the last two decades, many genetic and epigenetic changes in TAM and ML-DS have been elucidated. These include overexpression of molecules and micro-RNAs located on chromosome 21, GATA1 mutations, and a range of other somatic mutations and chromosomal alterations. In this review, we summarize molecular changes reported in TAM and ML-DS and provide a comprehensive and up-to-date discussion of these findings. Despite significant progress in this area, we still do not fully understand the pathogenesis of ML-DS and there are no targeted therapies. Initial diagnosis of ML-DS has a favorable prognosis, but refractory and relapsed disease can be difficult to treat, therapeutic options are limited by stronger toxicity of chemotherapy in DS children. Because of the rarity of this disease, large-scale multi-center studies would be helpful to advance molecular characterization of ML-DS at different stages of development and progression. New disease models are also required to test emerging therapeutic targets.